2021
DOI: 10.3390/ijerph18030943
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Emerging Pollutants (EPs) in Estuarine Water and Phytoremediation Capacity of Tripolium pannonicum under Controlled Conditions

Abstract: The increasing number of pharmaceuticals in the environment and their difficult biodegradation, can lead to bioaccumulation in different trophic compartments. Their bioaccumulation can have negative consequences, especially in the generation of bacterial resistance by antibiotics, but also in the impairment of plant and animal metabolism. The Tejo estuary in Portugal is the habitat for many plant and animal species, which are also prone to this type of contamination. Therefore, in the present study different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Industrial byproducts were defined as contaminants that are commonly used in industry such as fragrances (e.g., cashmeran, dihydrojasmonate), plastic production (e.g., bisphenol A, di-n-butyl phthalate), dyes (e.g., uranine), corrosion inhibitors (e.g., benzotriazole), and de-icing fluids (e.g., 5-methyl-1Hbenzotriazole). While these contaminants were not the focus of the review, they were observed in the primary studies and are often found in runoff from urban and agricultural landscapes [80,99,101,103,112,137,151,213].…”
Section: Source and Mixture Of Contaminant Types Entering Wetlandsmentioning
confidence: 99%
“…Industrial byproducts were defined as contaminants that are commonly used in industry such as fragrances (e.g., cashmeran, dihydrojasmonate), plastic production (e.g., bisphenol A, di-n-butyl phthalate), dyes (e.g., uranine), corrosion inhibitors (e.g., benzotriazole), and de-icing fluids (e.g., 5-methyl-1Hbenzotriazole). While these contaminants were not the focus of the review, they were observed in the primary studies and are often found in runoff from urban and agricultural landscapes [80,99,101,103,112,137,151,213].…”
Section: Source and Mixture Of Contaminant Types Entering Wetlandsmentioning
confidence: 99%
“…Halophytes are one of the most suitable models of salt stress tolerance mechanisms, due to their salt resistance [ 3 ]. The newest reports indicated that halophytes have considerable potential for the restoration of salt contaminated lands and potential for the phytosanitation and phytoremediation of the soil [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, analytical determinations of these compounds not only apply to the drugs manufacturing process but also to forensic science and for quantification of prohibited substances in doping [ 2 ] or drug abuse issues [ 3 ]. In addition, the growing demand for these compounds [ 4 ], together with the misuse that the population makes of them, cause wide pollution of waters and soils [ 5 ]. Consequently, knowing the concentration levels of these compounds in the environment, the body fluids and pharmaceutical formulations, could help in optimizing their use, also avoiding harmful effects they can cause [ 6 ].…”
Section: Introductionmentioning
confidence: 99%